Strength training for long-distance triathletes: theory to practice - Baldwin, K. M.; Badenhorst, C. E.; Cripps, A. J.; Landers, G. J.; Merrells, R. J.; Bulsara, M. K.; Hoyne, G. F. (Strength and Conditioning Journal, 2022)
Concurrent training, commonly acknowledged as a training method where strength and endurance training are completed complementary to each other, is a strategy often implemented in endurance cyclists' and runners' programs to improve physiological determinants of success such as exercise economy. Although concurrent training methods and strategies have been examined to a large extent in endurance cyclists and runners, literature examining optimal concurrent training methods to improve physiological variables in long-distance triathletes is minimal, leaving optimal programming relatively unknown. This practical applications paper identifies and outlines current concepts and considerations regarding concurrent training for long-distance triathletes including mechanisms contributing to improved performance, muscle and movement patterns used, exercise selection, load, velocity of movement, scheduling, frequency, and duration of training. Common misconceptions related to concurrent training are also identified and practical considerations for the application of concurrent training for coaches, athletes, and other professionals to improve all 3 disciplines of triathlon are discussed.